Financial guarantees required from life assurance concerns - Organisation for Economic Co-operation and Development (Paris : Organisation for Economic Co-operation and Development, 1971)
This report is broadly based on the programme of work established by the Working Party on financial guarantees required from life assurance concerns in a preliminary study which was approved by the insurance committee in December 1966 and June 1967. The whole of the preliminary study has been incorporated in the report and constitutes its first chapter. Next come the three analytical chapters, which have been elaborated on the basis of the programme of work already mentioned, and finally a chapter devoted to the procedure suggested for the multilateral application of the proposed solutions within the Organisation for Economic Co-operation and Development (OECD).
ne 08/05/2018
Loans
Keywords: Life Insurance